AKIBAT HUKUM MELAKUKAN DISKRIMINASI TERHADAP PENYEDIATRANSORTASI ONLINE - I Nyoman Suryana; Agustina Ni Made Ayu Darma Pratiwi (Jurnal Ilmiah Raad Kertha, 2023)
Transportation models consist of various types, of these transportation models motorbikes are included in the classification of types of private vehicles, but in Indonesia there are many motorcycles that also function as public transportation, namely transporting people and charging agreed fees. This type of transportation model is known as a motorcycle taxi. In the current era of globalization, there is an online transportation application model that has caught the attention of the public, namely online applicationbased transportation providers. The names that are known in the community are like gojek, grab, and so on. In the concept of a rule of law, both Continental Europe and Anglo Saxon, it is known that there is an element of protection of human rights and equality before the law, but regarding the operational area for online-based transportation service providers there are no national rules that regulate it so that it often creates legal problems between conventional transportation with online-based transportation.